Numerical Investigation of Phase-Conjugate Wave Generation as a Pulse Cleaner in Femtosecond Petawatt Laser Systems - Ziruo Cui; Xinglong Xie; Jun Kang; Qingwei Yang; Meizhi Sun; Ailin Guo; Haidong Zhu; Ping Zhu; Qi Gao; Xiao Liang; Simin Zhang; Jianqiang Zhu (IEEE Photonics Journal, 2019)
We report on comprehensive research regarding the potential of phase-conjugate wave (PCW) generation via backward degenerate four-wave mixing process as a pulse cleaner in femtosecond high-power laser systems. We analyzed the performance of this technique by investigating the contrast enhancement capability, gain bandwidth, and energy conversion efficiency. All of these parameters are important in pulse cleaning. The numerical calculations verified that a considerably large efficiency bandwidth product and an excellent contrast enhancement capability can be realized by finding a balance between each physical effect. The simulation results based on this study provide guidance for the application of this technique in laser systems with different bandwidths. The method, which is based on PCW generation, provides new insights for femtosecond petawatt laser systems as pulse cleaners.